A Systematic Study on Callicarpa L. (Verbenaceae) in Borneo - Abraham-Oanes, Gloria (2002)
A systematic study on the Bornean Callicarpa (Verbenaceae) was undertake n utilising m ore than 1,200 collections from fourteen herbaria. A total of 37 taxa were recognised and twenty-two taxa are undoubtedly endemic to the island. Two new species namely , C. hanumiae and C. argentii were described and illustrated while two new record s , i.e., C. ramiflora and C. arborea for Borneo were made . Five formerly recognised varieties such as C. havilandii var. hispida , C. japonica var. rhombifolia, C. kinabaluensis var. endertii, C. kinabaluensis var. gibotii and G. hexandra var. macrophylla while three forms viz. C. longifolia f. floccosa, C. longifolia f. subglabrata and C. pentandra var. typica f. hexandra were raised to species and variety levels, respectively. The other two forms, C. pentandra var. typica f. farinosa and C. pentandra var . paloensis f. apoensis were likewise raised to distinct varieties. All Bornean Geunsia reduced to Callicarpa by Lam and Bakhuizen van den Brink (1921) is basically supported by the present study. Several approaches such as morphology, anatomy, palynology, ecology and phytogeography were employed to species delimitation. Many characters obtained from these lines of evidences were proven to have taxonomic value. The leaf shape, margin, size of the lamina, degree of hairiness of leaf surfaces and petioles and leaf base, were among the diagnostic vegetative morphological characters. Taxonomically valuable reproductive characters include the point of insertion of the inflorescence, type of the inflorescence's indumentum, length of the peduncle, the colour of the corolla, the hairiness of the outside lobe of the calyx and calyx margin. The pattens of the vascular bundles in the petiole, the minor leaf venation patterns and the cuticular ornamentation were acknowledged as new diagnostic anatomical characters in species identification and delimitation in addition to other useful characters such as stomata and trichomes. The stomata are anomocytic in most species and mostly hypostomatic in its orientation.